Evaluating the effectiveness of EGGA (English Grammar Guide Application) for grammar learning / Lilly Metom ... [et al.] - Metom, Lilly; Noyan, John Francis; Ibrahim, Sueb; Bohari, Zubaidah; Abdul Talip, Abdul Hadi (Universiti Teknologi MARA Cawangan Sarawak, 2024)
This paper evaluates the effectiveness of EGGA – an English Grammar Guide Application, a mobile-assisted language learning tool for grammar acquisition that serves as a supplementary grammar learning aid for non-native English learners. The mobile application is designed as a self-directed evaluation tool that enables learners to learn basic English grammar and self-evaluate their learning outcomes. The study involved 54 diploma students from UiTM Sarawak and used a Usability Instrument to gauge their satisfaction with EGGA's multimedia elements and usefulness. The results indicate that EGGA was well-received by the participants, with high mean scores for all multimedia elements, including graphics, sound, interactivity, text, interface, and usefulness. The application was found to be effective in motivating learners to acquire and improve their grammar skills, creating a fun and interactive learning experience, and providing a mechanism for self-assessment. Based on these findings, EGGA can be concluded to be a useful and practical tool for learners of any age group to learn target grammar, serving as an effective supplementary tool for self-directed language learning.